Development of indicators for avoidable emergency medical service calls by mapping paramedic clinical impression codes to ambulatory care sensitive conditions and mental health conditions in the UK and Canada - Kamlesh Khunti; Robert Spaight; Niro Siriwardena; Gina Agarwal; Graham Law; Melissa Pirrie; Ricardo Angeles; Mark Gussy; Brent McLeod; Aloysius Niroshan Siriwardena; Gregory Whitley; Bartholomew Hill; et al. (BMJ Open)
Objective Paramedic assessment data have not been used for research on avoidable calls. Paramedic impression codes are designated by paramedics on responding to a 911/999 medical emergency after an assessment of the presenting condition. Ambulatory care sensitive conditions (ACSCs) are non-acute health conditions not needing hospital admission when properly managed. This study aimed to map the paramedic impression codes to ACSCs and mental health conditions for use in future research on avoidable 911/999 calls.Design Mapping paramedic impression codes to existing definitions of ACSCs and mental health conditions.Setting East Midlands Region, UK and Southern Ontario, Canada.Participants Expert panel from the UK-Canada Emergency Calls Data analysis and GEospatial mapping (EDGE) Consortium.Results Mapping was iterative first identifying the common ACSCs shared between the two countries then identifying the respective clinical impression codes for each country that mapped to those shared ACSCs as well as to mental health conditions. Experts from the UK-Canada EDGE Consortium contributed to both phases and were able to independently match the codes and then compare results. Clinical impression codes for paramedics in the UK were more extensive than those in Ontario. The mapping revealed some interesting inconsistencies between paramedic impression codes but also demonstrated that it was possible.Conclusion This is an important first step in determining the number of ASCSs and mental health conditions that paramedics attend to, and in examining the clinical pathways of these individuals across the health system. This work lays the foundation for international comparative health services research on integrated pathways in primary care and emergency medical services.